"Public Health Behaviors during the COVID-19 Pandemic in Greece and Associated Factors: A Nationwide Cross-sectional Survey". (May 2021) - Souliotis, Kyriakos; Giannouchos, Theodoros V.; Peppou, Lily E.; Samara, Myrto T.; Nimatoudis, John; Papageorgiou, Charalambos; Economou, Marina
The objective of this cross-sectional survey was to estimate the association between multiple socioeconomic, and health-related characteristics, COVID-19 related attitudes and adoption of public health preventive behaviors. A national cross-sectional survey among 1205 adults was conducted in April 2020 in Greece. Multivariable ordered logistic regression models were used to estimate the association between COVID-19 related attitudes and knowledge and adoption of preventive behaviors, controlling for socioeconomic and health-related characteristics. A total of 923 individuals fully completed the survey. Individuals who believed that the virus is out of control, is transmitted through the air, and is not similar to the common flu were more likely to adopt public health preventive behaviors more frequently, particularly wearing masks in public spaces, washing their hands, and spending fewer hours out of their homes. Uncertainty about the virus symptomatology was associated with less frequent mask-wearing and handwashing. Increased social support, frequent media use for COVID-19 updates, trust to authorities, older age, worse health status, female gender and being a healthcare professional were also associated with uptake of some preventive health behaviors. Attitudinal and socioeconomic determinants critically affect public engagement in preventive behaviors. Health policy initiatives should focus on community outreach approaches to raise awareness and to strengthen social support mechanisms by integrating multiple stakeholders.